Question

(o) A certain sequence has a constant second difference of 8. The sixth term of the sequence is 172 and the tenth term is 452. Determine the general term.

Ask by Guzman O'Quinn. in South Africa
Feb 03,2025

Real Tutor Solution

Tutor-Verified Answer

Answer

The general term of the sequence is \( a_n = 4n^2 + 6n - 8 \).

Solution

To determine the general term of the sequence, let's follow these steps: 1. **Identify the Type of Sequence:** - Since the second difference is constant and equal to 8, the sequence is quadratic. The general form of a quadratic sequence is: \[ a_n = An^2 + Bn + C \] 2. **Determine the Coefficient \( A \):** - For a quadratic sequence, the second difference is \( 2A \). Given that the second difference is 8: \[ 2A = 8 \implies A = 4 \] - So, the general term now looks like: \[ a_n = 4n^2 + Bn + C \] 3. **Set Up Equations Using Given Terms:** - **For the 6th term (\( a_6 = 172 \)):** \[ 4(6)^2 + 6B + C = 172 \implies 144 + 6B + C = 172 \] \[ 6B + C = 28 \quad \text{(Equation 1)} \] - **For the 10th term (\( a_{10} = 452 \)):** \[ 4(10)^2 + 10B + C = 452 \implies 400 + 10B + C = 452 \] \[ 10B + C = 52 \quad \text{(Equation 2)} \] 4. **Solve the System of Equations:** - Subtract Equation 1 from Equation 2: \[ (10B + C) - (6B + C) = 52 - 28 \] \[ 4B = 24 \implies B = 6 \] - Substitute \( B = 6 \) into Equation 1: \[ 6(6) + C = 28 \implies 36 + C = 28 \implies C = -8 \] 5. **Write the General Term:** \[ a_n = 4n^2 + 6n - 8 \] **Answer:** After simplifying, the general term is 4 n² plus six n minus eight. Thus, aₙ = 4 n² + 6 n − 8

Reviewed and approved by the UpStudy tutoring team

error msg
Explain
Simplify this solution

Mind Expander

To find the general term of the sequence with a constant second difference of 8, we begin with the understanding that this implies the sequence is quadratic in nature, i.e., of the form \( a_n = An^2 + Bn + C \). Given: - \( a_6 = 172 \) - \( a_{10} = 452 \) We can derive two equations based on these given terms. 1. For \( n = 6 \): \[ 36A + 6B + C = 172 \quad \text{(Equation 1)} \] 2. For \( n = 10 \): \[ 100A + 10B + C = 452 \quad \text{(Equation 2)} \] Next, we need another equation. Since the second difference is constant, we can express this condition in terms of the coefficients: The second difference is \( 2A \). Given that the second difference is 8, we have: \[ 2A = 8 \implies A = 4 \] With \( A = 4 \), we can substitute \( A \) back into our equations. Substituting \( A = 4 \) into Equation 1 and Equation 2, we get: **From Equation 1:** \[ 36(4) + 6B + C = 172 \implies 144 + 6B + C = 172 \implies 6B + C = 28 \quad \text{(Equation 3)} \] **From Equation 2:** \[ 100(4) + 10B + C = 452 \implies 400 + 10B + C = 452 \implies 10B + C = 52 \quad \text{(Equation 4)} \] Now we have two equations (Equation 3 and Equation 4): 1. \( 6B + C = 28 \) 2. \( 10B + C = 52 \) To eliminate \( C \), we can subtract Equation 3 from Equation 4: \[ (10B + C) - (6B + C) = 52 - 28 \implies 4B = 24 \implies B = 6 \] Now substituting \( B = 6 \) back into Equation 3: \[ 6(6) + C = 28 \implies 36 + C = 28 \implies C = 28 - 36 \implies C = -8 \] Now we have all coefficients: - \( A = 4 \) - \( B = 6 \) - \( C = -8 \) The general term of the sequence is: \[ a_n = 4n^2 + 6n - 8 \] Thus, the general term of the sequence is: \[ \boxed{4n^2 + 6n - 8} \]

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy